Kepentingan Umum dalam Perlindungan Hak Cipta di Indonesia - ismayana ismayana (Fakultas Hukum Universitas Swadaya Gunung Jati, 2015)
AbstractOne of the agreements reached by the Agreement Establishing the World Trade Organization (WTO) is the Agreement on Aspects of Intellectual Property Rights Related Trade (TRIPS ). Through TRIPS developed countries calls for setting the protection and enforcement of protection of intellectual property rights. The purpose of this research was to determine the nature of the public interest in the protection of Copyright and whether the public interest is a major cornerstone in the protection of Copyright. The research method used is the method of normative, descriptive and to determine public interest in the protection of rights Cipta.This study stated that the provisions of the Berne Convention, TRIPS, and the Copyright Act of each state normatively recognize and protect the public interest Copyright protection, but today there are efforts to suppress public interest in the protection of intellectual property rights by means of the developed countries require strict protection standard, a standard known as